Crossers in a Segmented Labour Market: Occupational Advancement and Wage Changes from Semi-Skilled and Unskilled Jobs - Philip Wotschack; Claire Samtleben (Work, Employment and Society, 2024)
How the upward mobility chances of workers in unskilled or semi-skilled jobs are shaped by influences at the organisational and sectoral level remains an open question. This article aims to close this research gap by examining the role of internal labour market characteristics in the promotion prospects and wage increases of workers in semi-skilled and unskilled positions. The hypotheses are derived from dual and segmented labour market theory. Regression analyses based on linked-employer-employee-data (LIAB), covering 44,024 workers in semi-skilled and unskilled positions from 2005 to 2010, underline the importance of the internal labour market. A considerable share of workers moved to skilled positions through company change. For the workers who stayed with the company, career advancements were associated with regular training investments and formalised regulations at the company level. Collective agreements, in contrast, were associated with lower chances of upward mobility, but higher wages.
Keywords: 330; (in)equality and discrimination; policy and regulation; skills and training